TrueWeb: A Proposal for Scalable Semantically-Guided Data Management and Truth Finding in Heterogeneous Web Sources - Madkour, Amgad; Aref, Walid G.; Prabhakar, Sunil; Ali, Mohamed; Bykau, Siarhei (SIGMOD Semantic Big Data, 2018)
We envision a responsible web environment, termed TrueWeb, where a user should be able to find out whether any sentence he or she encounters in the web is true or false. The user should be able to track the provenance of any sentence or paragraph in the web. The target of TrueWeb is to compose factual knowledge from Internet resources about any subject of interest and present the collected knowledge in chronological order and distribute facts spatially and temporally as well as assign some belief factor for each fact. Another important target of TrueWeb is to be able to identify whether a statement in the Internet is true or false. The aim is to create an Internet infrastructure that, for each piece of published information, will be able to identify the truthfulness (or the degree of truthfulness) of that piece of information.